Implikasi Hukum Terhadap Perlindungan Konsumen Dalam Era Digital - Muhammad Hafis; Delvi Yusril; Yulius Rico Adrianto; Rivaldi (CV. ITTC INDONESIA, 2024)
Everyone does not rule out the possibility of facing risks due to the actions they take. This risk can originate from agreements and/or laws and regulations which result in losses for consumers, so they must be responsible for their legal actions, and to obtain legal protection for consumers in the digital era. Therefore, in order to avoid the risk of greater loss, someone can apply for self-insurance, remembering that the purpose of insurance is to transfer the risk of violations to consumers in the digital era. The formulation of this research problem is Legal Implications for Consumer Protection in the Digital Era? This research uses a normative method with a statutory and conceptual approach, as well as secondary data in the form of primary legal materials and secondary legal materials with a conceptual analysis approach presented in the form of analytical descriptive narratives.